2022
DOI: 10.1001/jamanetworkopen.2022.44772
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal and Child Anemia With Brain Structure in Early Life in South Africa

Abstract: ImportanceAnemia affects millions of pregnant women and their children worldwide, particularly in low- and middle-income countries. Although anemia in pregnancy is a well-described risk factor for cognitive development, the association with child brain structure is poorly understood.ObjectiveTo explore the association of anemia during pregnancy and postnatal child anemia with brain structure in early life.Design, Setting, and ParticipantsThis neuroimaging nested cohort study was embedded within the Drakenstein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 68 publications
0
11
1
Order By: Relevance
“…Previous studies examining the relationship between maternal iron status and neurodevelopment aged 4-5 years have shown mixed results, with either no association 24 , or possible positive benefit from higher maternal iron status on memory 25 and attention 26 . A small South African study specifically assessing brain morphology found that maternal anemia, but not childhood anemia, was associated with smaller brain volumes and altered structural brain development at 2-3 years 27 .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Previous studies examining the relationship between maternal iron status and neurodevelopment aged 4-5 years have shown mixed results, with either no association 24 , or possible positive benefit from higher maternal iron status on memory 25 and attention 26 . A small South African study specifically assessing brain morphology found that maternal anemia, but not childhood anemia, was associated with smaller brain volumes and altered structural brain development at 2-3 years 27 .…”
Section: Results In the Context Of What Is Knownmentioning
confidence: 99%
“…Findings regarding the association between antenatal maternal anaemia and child brain structure at 2–3 years of age in this cohort have been published [ 4 ]. The current study is focused on the 6–7 year timepoint, at which 157 children had both useable structural neuroimaging data (see neuroimaging measures section below) and maternal haemoglobin data for inclusion in analysis.…”
Section: Methodsmentioning
confidence: 99%
“…While the importance of this first 1000-day window is well-known, recent research is providing increasing evidence to support a renewed focus on optimising antenatal maternal well-being for improved neurodevelopmental outcomes in children [ 1 ]. In recognizing the foetal origins of brain health and the persistent impact of early risk, maternal anaemia during pregnancy is an important health priority for targeted prevention and intervention strategies [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…maternal diabetes and hypertension), showing low cord ferritin levels at delivery are related to slower auditory brainstem responses in neonates tested 48 hours after birth (Amin et al 2013). Further evidence related to iron and brain development comes from work demonstrating maternal somatic iron during pregnancy was related to infant brain volume (Wedderburn et al 2022).…”
Section: Introductionmentioning
confidence: 99%